2002
DOI: 10.1046/j.1442-2026.2002.00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous suicide in Australia, New Zealand, Canada and the United States

Abstract: This paper reviews literature on self‐harm and suicide among Indigenous populations in four nations with histories of British colonization, with a more detailed exploration of patterns and primary care considerations in Australian Aboriginal and Torres Strait Islander populations. Issues of definition, under‐reporting, lack of reporting, varying coronial practices and the influence of race on investigative procedures make comparisons of suicide rates among indigenous populations problematic. However, internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(90 citation statements)
references
References 32 publications
6
83
1
Order By: Relevance
“…In some cases, the rates of suicide are five times the rate of the general population (26). Similar results have been found when comparing rates of alcohol use, post-traumatic stress and depression (54)(55)(56).…”
Section: Future Researchsupporting
confidence: 71%
See 1 more Smart Citation
“…In some cases, the rates of suicide are five times the rate of the general population (26). Similar results have been found when comparing rates of alcohol use, post-traumatic stress and depression (54)(55)(56).…”
Section: Future Researchsupporting
confidence: 71%
“…The strongest associations were observed for mental health outcomes (psychological stress and depression) and health-related behaviours (substance abuse, alcohol abuse and smoking). Rates of substance and alcohol abuse are substantially higher among Indigenous groups, which have also been shown to be related to increased rates of suicide (26). A review of suicide rates among Indigenous populations in Canada, the U.S., New Zealand and Australia found that suicide rates among Indigenous young adult men was the highest out of all age groups and was 2 to 5 times higher than the general population (26).…”
Section: Ethnicity Culture and Racementioning
confidence: 99%
“…The Aboriginal population plummeted to 50,000 by the 1890s through introduced diseases, dispossession of land, massacres and covert frontier wars (Flannery 1994). Current day Aboriginal health and mental health is considerably worse than for non-Aboriginal Australians and while the health of comparable populations in other first world countries have improved, Australian Aboriginal people still fare poorly comparatively (Hunter and Harvey 2002;Zubrick et al 2004). For example, while the life expectancy of Canadian, USA and New Zealand indigenous peoples is 5-7 years less than their non-Indigenous country people, Aboriginal Australians still die 20 years earlier than non-Aboriginal Australians (Hunter and Harvey).…”
Section: Experiences Of Aboriginal Australians and Policymentioning
confidence: 98%
“…Premature mortality from substance misuse and suicide is also high in indigenous communities around the world, reflecting current and historical trauma, discrimination and disempowerment (Hunter and Harvey, 2002;Evans-Campbell, 2008;Wilk et al, 2017).…”
Section: An International Contextmentioning
confidence: 99%